The house of forking paths. a walk through the illustrious guest´s house by rogelio salmona in cartagena (2009)
This article is an analysis of the Illustrious Guest´s house in Cartagena Colombia by the architect Rogelio Salmona. A comparison of the current project with a hypothetical version of it is the tool to establish that there is a common design procedure used throughout the house. The text studies how this design strategy is used in other projects by the same author and how it is put into practice at different scales. Finally, the article intends to demonstrate how the house encourages a particular experience of time and motion in the building.